Consumer Complaining Behavior in Hospitality Management - Tosun, Petek; Sezgin, Selime; Uray, Nimet (Taylor & Francis, 2021)
The purpose of this study is to investigate the impacts of assertiveness, aggressiveness, and perceived risks on consumer complaining behavior (CCB) in the tourism and hospitality sector. This research utilized a quantitative methodology through the implementation of a two-stage study based on surveys. Study 1 examined the impacts of assertiveness, aggressiveness, and perceived risks on CCB in the context of low-quality summer vacation, while Study 2 further investigated the relationships in the research model by replicating the survey within the framework of high-quality summer vacation. The results were then analyzed through factor and regression analyses. Both of the studies demonstrated that assertiveness positively influences CCB directly and also indirectly via the mediating effect of perceived risks. It was found that aggressiveness positively influences CCB when consumers have high service quality expectations but when they have low expectations for service quality, it is insignificant.
Keywords: Service failures; Tourism; Consumer complaining behavior; Aggressiveness; Perceived risks; Assertiveness